Establishing survey validity: A practical guide - William Cobern; Betty Adams (International Journal of Assessment Tools in Education)
What follows is a practical guide for establishing the validity of a survey for research purposes. The motivation for providing this guide is our observation that researchers, not necessarily being survey researchers per se, but wanting to use a survey method, lack a concise resource on validity. There is far more to know about surveys and survey construction than what this guide provides; and this guide should only be used as a starting point. However, for the needs of many researchers, this guide provides sufficient, basic information on survey validity. The guide, furthermore, includes references to important handbooks for researchers needing further information.